2023
DOI: 10.3390/molecules28020477
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Local Anesthetic Activity, Acute Toxicity, and Structure–Toxicity Relationship in Series of Synthesized 1-Aryltetrahydroisoquinoline Alkaloid Derivatives In Vivo and In Silico

Abstract: Isoquinoline alkaloids constitute one of the most common classes of alkaloids that have shown a pronounced role in curing various diseases. Finding ways to reduce the toxicity of these molecules and to increase their therapeutic margin is an urgent matter. Here, a one-step method for the synthesis of a series of 1-aryl-6,7-dimethoxy-1,2,3,4-tetrahydroisoquinolines was performed in 85–98% yield by the Pictet–Spengler reaction. This was accomplished using the reaction between 3,4-dimethoxyphenylethylamine and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Upon discovering the ability of galangin to inhibit the synthesis of pro-inflammatory mediators, specifically histamine and prostaglandins, induced by carrageenan and formalin, as well as its capacity to hinder acute inflammation and prevent the activation of pain-sensing nerve endings, this investigation delved deeper into the serum and local tissue levels of TNF-α, IL-6, IL-1β, IL-10, COX-2, and PGE2 in rats experiencing capsaicin-induced inflammatory pain. These findings revealed that galangin effectively suppresses the production and levels of these pro-inflammatory mediators, which aligns with previous studies on the efficacy of anti-inflammatory analgesic drugs [ 26 , 28 ]. This further suggests that galangin may inhibit cyclooxygenase activity, thus reducing prostaglandin synthesis and suppressing the levels of pro-inflammatory mediators to impede the development of inflammatory pain.…”
Section: Discussionsupporting
confidence: 91%
“…Upon discovering the ability of galangin to inhibit the synthesis of pro-inflammatory mediators, specifically histamine and prostaglandins, induced by carrageenan and formalin, as well as its capacity to hinder acute inflammation and prevent the activation of pain-sensing nerve endings, this investigation delved deeper into the serum and local tissue levels of TNF-α, IL-6, IL-1β, IL-10, COX-2, and PGE2 in rats experiencing capsaicin-induced inflammatory pain. These findings revealed that galangin effectively suppresses the production and levels of these pro-inflammatory mediators, which aligns with previous studies on the efficacy of anti-inflammatory analgesic drugs [ 26 , 28 ]. This further suggests that galangin may inhibit cyclooxygenase activity, thus reducing prostaglandin synthesis and suppressing the levels of pro-inflammatory mediators to impede the development of inflammatory pain.…”
Section: Discussionsupporting
confidence: 91%
“…In a recent study, Azamatov et al introduced computational AMDET prediction methods to develop novel local anesthetics with lower toxicity. Through the study of a group of 1-aryl tetrahydroisoquinoline alkaloid derivatives, they also proposed explainable correlations between chemical structures and acute toxicity [152]. Another approach is to refine currently available drugs by optimizing PK/PD parameters.…”
Section: Evaluation Of Admet Propertiesmentioning
confidence: 99%